Innovation and Economic Sustainability: A Bibliometric Perspective on Global Research Trends - Jumiati, Eti; Adi Cahya, Willy (Yayasan Meira Visi Persada, 2025)
Innovation has become a key factor in supporting economic sustainability in the era of digital transformation and globalization. This study aims to analyze global research trends on the relationship between innovation and economic sustainability using a bibliometric approach. By utilizing the Scopus database, this study identifies publication patterns, main themes, and academic collaboration networks in this field. VOSviewer and Biblioshiny software. The data collected includes scientific publications from 2005 to 2025, which are then analyzed based on publication trends, keyword relevance, and collaboration patterns between researchers and institutions. The literature selection process follows the PRISMA method, ensuring that only relevant and high-quality articles are used in the analysis. The results show that the number of publications related to innovation and economic sustainability increased significantly after 2020, reflecting the increasing attention to digital transformation, green economy, and sustainable innovation. Key keywords that frequently appear in this study include sustainable innovation, economic sustainability, and technological innovation, which are closely related to the concepts of circular economy, corporate social responsibility ( CSR ), and corporate governance. The collaboration map shows that China and European countries such as Italy and the UK play a leading role in this research, while emerging countries such as Indonesia and Brazil are starting to contribute to the global academic discussion. The implication of this study is that innovation has a broad impact on economic sustainability, both in terms of industrial growth, resource efficiency, and environmental sustainability. These findings can be a basis for policy makers and business practitioners in developing innovative strategies oriented towards sustainability. In addition, the results of this study also indicate the need to strengthen cross-country academic cooperation to accelerate the adoption of innovations that support sustainable economic development